经济相互依赖对两岸政治关系走向的影响 ：以ECFA为研究个案 = The implications of economic interdependence on cross-strait political relations : a research based on the case study of ECFA - 郑裕祥 Tay, Yuxiang (2013)
在过去的几十年里，两岸的经济活动，这主要是由内地和台湾政府的政治议程。在这样一个有趣的和计算的政治环境，两岸经济决策的合理性已经受到严重损害。而不是利润最大化，通过投资和贸易，政治内斗，在两国政府和争吵不休国家的身份成为了主要的，经常的，在制定经济政策的唯一考虑因素. The Cross-Strait economic activities for the past few decades were largely dictated by the political agendas of the Mainland and the Taiwanese governments. In such an intriguing and calculating political environment, the soundness of Cross-Strait economic decisions has been seriously compromised. Rather than maximizing profits through investment and trade, political in-fighting within the two governments and bickering over national identities became the major, and often, the sole consideration in the formulation economic policies. Consequently, the development and implementation of many sound economic policies aimed at improving Cross-Strait economic ties have been unnecessarily obstructed. The coordination among the various agencies responsible for policy formulation has often been rendered inefficient. As a result, valid and important economic concerns of various Taiwanese entities that engage in economic activities with the Mainland have often been ignored. Then, on 29 June 2010, the historical Cross-Strait Economic Cooperation Framework Agreement (ECFA) was signed between Taiwan and China. This milestone agreement came into effect on 12 September 2010. While the Kuomintang government claims that ECFA is key to a vibrant economy in the future, the opposition Democratic People’s Party (DPP) argues that the potential costs of the ECFA far outweigh any future benefits. Rather than spurring economic growth, opening the domestic market to Mainland companies would only hurt the local economy and would eventually result in the Taiwanese economy becoming over-dependent on the Mainland economy. The DPP further criticizes that although the apparent aim of the ECFA is to promote Cross-Strait economic exchanges, it is in fact no more than a thinly veiled Trojan horse that would eventually cause uncertainties and damage to the security, strategic and political futures of Taiwan. This thesis aims to discuss the likely trajectory of the Cross-Strait political relations in the post-ECFA era by employing the economic interdependence theory, the international relations theory, and by constructing a dynamic game theory model.